ANALISA AWAL PENINJAUAN KEMBALI RENCANA TATA RUANG WILAYAH (RTRW) KABUPATEN PENUKAL ABAB LEMATANG ILIR - Desi Ika Ariyanti; Kiagus Muhammad Aminuddin; Bochori Bochori; Fajar Sadik Islami; Irma Indriani (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2026)
Rapid development dynamics and the update of spatial planning regulations at both national and regional levels require spatial plans to remain adaptive and relevant. This study aims to evaluate the necessity of reviewing Regional Regulation No. 1 of 2018 concerning the Regional Spatial Plan (RTRW) of Penukal Abab Lematang Ilir (PALI) Regency for the 2018–2038 period. The evaluation was conducted comprehensively through two main approaches: a synchronization analysis of spatial utilization against the latest legal frameworks, and a spatial data analysis to assess the quality, validity, and deviations of spatial utilization. The evaluation reveals that the current RTRW content requires significant refinement. In terms of spatial structure, the existing document covers only 76.29% of the required parameters, with a plan depth score of just 36.72%. Critical infrastructure elements, such as local roads, environmental roads, and energy networks, remain insufficiently planned. Meanwhile, the spatial pattern element achieved an 87.50% completeness rate and a 75.00% depth rate, yet still omits strategic areas such as aquaculture and transportation zones. Furthermore, the implementation of the first five-year program shows low execution rates, most notably the delay in establishing Detailed Spatial Plans (RDTR) for designated activity centers. This study concludes that the RTRW of PALI Regency urgently requires a formal revision to integrate updated policy directions and align spatial utilization with actual regional development dynamics.